A experiência do cliente de empresas de telecomunicações: uma proposta de metodologia para sua mensuração e análise considerando aspectos regionais - Resende, Sthéfani Lorena Ribeiro (2019)
This research aimed to measure the perception of client experience in telecommunication companies considering the customer journey. This subject customer experience is recent; publications on this matter only started to increase significantly in 2010, when 423 studies were published. From this date to June 2017, 3,528 studies on customer service were published. Based on a search in academic databases, we identified a gap on the definition of customer experience and on the measurement of this experience. Thus, the following aspects justify this study: (a) the lack of a consistent definition of what client experience is; (b) the non-existence of a methodology to measure clients’ overall experience and in each stage of the customer journey; (c) the importance of client experience to develop a link between clients and organizations, which creates value for the company and, consequently, builds customer loyalty; (d) the fact that experience is considered the standard of customer satisfaction; (e) the comparison this study proposes between the perception of customer experience in a regional company with that of other companies operating nationally – we analyzed customers’ perception in the Brazilian region of Triângulo Mineiro and Alto Paranaíba and southern Goiás, by comparing them with clients of telecommunication companies from other regions of Brazil. Based on this scenario, we proposed a theoretical model to analyze the following constructs: the overall client experience in telecommunications and customer experience at every stage of the customer journey in telecommunications. This study adopted the quantitative method, which proposes and validates a methodology to measure experience. In the first phase of this stage, we followed six steps to build measurement scales proposed by Vieira (2011): (i) construct definition; (ii) elaboration of items that access the construct; (iii) content validation of indicators; (iv) application of indicators in a pretest survey; (v) application of the scale in an official study; and (vi) performance of studies to validate the construct. Regarding the official study, an on-line survey was published on social networks requesting that interviewees answered several questions about their experiences with telecom companies of which they are clients. We obtained 521 valid responses. The proposed customer experience with telecommunication services scale was an 11-point Likert type containing four indicators of experience: poor to pleasant; miserable to happy; non-memorable to memorable; and satisfaction with experience. The scale was validated and presented a Cronbach's alpha of 0.951. Next, we measured the overall customer experience, which resulted in 6.3105, and the stages of the customer journey, which resulted in 5.3238 in the experience with propaganda, 6.2663 in the experience when searching about the telecom company, 6.6065 in the experience with payment (this stage had the best perception), 6.67121 in the use experience, 6.2392 in the experience with customer service, 6.0526 in the experience with maintenance, and 5.3684 in the experience with cancellation. We also compared the perception of client experience in a regional telecommunication company in Triângulo Mineiro with other companies in the same sector with national reach. The result showed that the overall experience is greater in the regional company than in the others, which is also identified in the stages of the customer journey. And the comparison between the customers' perception of the Triângulo Mineiro, Alto Paranaíba and the South of Goiás, and the perception of customers in other regions of the country regarding their experiences as clients of telecommunications companies, which resulted in the average experience being with the clients of the study's focus region than in the other regions of Brazil, when comparing the experience in the different stages of the client's journey, the same result was reflected. The results of regressions indicated that the variation in the overall experience is 72%, explained by experiences in the stages of use, maintenance, and service contracting. Regarding the local company, 77.2% of variation in the overall experience is explained by experiences in the stages of use, maintenance, and service contracting. Regarding the national companies, 68% of variation in the overall experience is explained by experiences in the stages of use and maintenance. Regarding local clients, 73.6% of variation in the overall experience is explained by experience in the stages of use, maintenance, and search about the telecom company. In the regression of national clients, the overall experience is explained in 83.2% by experiences in the stages of use, maintenance, and search about the telecom company.